2020
DOI: 10.5195/ijt.2020.6308
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Practitioners’ Determinants of Telerehabilitation Acceptance

Abstract: Background: Pulmonary rehabilitation is a multidisciplinary patient-tailored intervention that aims to improve the physical and psychological condition of people with chronic respiratory diseases. Providing pulmonary rehabilitation (PR) services to the growing population of patients is challenging due to shortages in health care practitioners and pulmonary rehabilitation programs. Telerehabilitation has the potential to address this shortage in practitioners and PR programs as well as improve patients’ partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…Although there was no relationship between "satisfaction with the development of the clients" and "the number of sessions they held in the last month", this finding could be considered within the scope of the Technology Acceptance Model [27] More online sessions of SLTs, who reported that they had been satisfied with using their clinical skills in telepractice, emphasized how important perceived usefulness and utility were on attitudes. This finding was consistent with the findings of some telepractice (telepractice, telerehabilitation) studies [4,[38][39][40][41]. It became prominent once again that the more clinicians take a technology useful, the easier it is to adapt to these technologies.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Although there was no relationship between "satisfaction with the development of the clients" and "the number of sessions they held in the last month", this finding could be considered within the scope of the Technology Acceptance Model [27] More online sessions of SLTs, who reported that they had been satisfied with using their clinical skills in telepractice, emphasized how important perceived usefulness and utility were on attitudes. This finding was consistent with the findings of some telepractice (telepractice, telerehabilitation) studies [4,[38][39][40][41]. It became prominent once again that the more clinicians take a technology useful, the easier it is to adapt to these technologies.…”
Section: Discussionsupporting
confidence: 89%
“…The issue that needs to be emphasized here is the importance of the "perceived convenience" factor within the scope of the Technology Acceptance Model [27]. The easier the usage of these systems is perceived in the beginning, the more positive user attitudes are [38] In their study, Bradford et al [14] stated that most of the practitioners whose opinions they received initially doubted that telepractice would be effective and thought that the therapeutic relationship could not be established, but they concluded that their negative opinions on this issue changed in the opposite direction as the telepractice sessions progressed. Similarly, in our study, SLTs who performed telepractice sessions before the pandemic did not have any difficulty in providing telepractice services during the pandemic process.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence supports that perceived usefulness is a predictor to positive intentions to use telerehabilitation. 27 Dahl-Popolizio et al examined the effectiveness of OT services during the COVID-19 pandemic, and reported that OTs felt that conditions of the hand and upper extremity could effectively be treated via telehealth and that therapeutic exercise and home programs could be delivered with telehealth. 28 Currently, the evidence related to efficacy of telehealth in hand rehabilitation as it relates to certain conditions or treatment approaches is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Technology use, according to the unified theory of acceptance and use of technology (UTAUT), depends on performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, price and habit, which are moderated by age, gender, and experience (UTAUT2) [26]. It has been reported that in professionals perceived usefulness is a predictor of telerehabilitation use [34], and in patients affordability and accessibility are facilitators for using telerehabilitation [34].…”
Section: Discussionmentioning
confidence: 99%